Outer membrane biogenesis in Escherichia coli, Neisseria meningitidis, and Helicobacter pylori: paradigm deviations in H. pylori - Liechti, George W.; Goldberg, Joanna B. (Frontiers in Cellular and Infection Microbiology, 2012)
The bacterial pathogen Helicobacter pylori is capable of colonizing the gastric mucosa of the human stomach using a variety of factors associated with or secreted from its outer membrane (OM). Lipopolysaccharide (LPS) and numerous OM proteins have been shown to be involved in adhesion and immune stimulation/evasion. Many of these factors are essential for colonization and/or pathogenesis in a variety of animal models. Despite this wide array of potential targets present on the bacterial surface, the ability of H. pylori to vary its OM profile limits the effectiveness of vaccines or therapeutics that target any single one of these components. However, it has become evident that the proteins comprising the complexes that transport the majority of these molecules to the OM are highly conserved and often essential. The field of membrane biogenesis has progressed remarkably in the last few years, and the possibility now exists for targeting the mechanisms by which β-barrel proteins, lipoproteins, and LPS are transported to the OM, resulting in loss of bacterial fitness and significant altering of membrane permeability. In this review, the OM transport machinery for LPS, lipoproteins, and outer membrane proteins (OMPs) are discussed. While the principal investigations of these transport mechanisms have been conducted in Escherichia coli and Neisseria meningitidis, here these systems will be presented in the genetic context of ε proteobacteria. Bioinformatic analysis reveals that minimalist genomes, such as that of Helicobacter pylori, offer insight into the smallest number of components required for these essential pathways to function. Interestingly, in the majority of ε proteobacteria, while the inner and OM associated apparatus of LPS, lipoprotein, and OMP transport pathways appear to all be intact, most of the components associated with the periplasmic compartment are either missing or are almost unrecognizable when compared to their E. coli counterparts. Eventual targeting of these pathways would have the net effect of severely limiting the delivery/transport of components to the OM and preventing the bacterium's ability to infect its human host.